DEVELOPMENT OF LOCAL WISDOM-BASED E-FLIPBOOKS FOR UNDERSTANDING ENGLISH VOCABULARY FOR STUDENTS WITH DISABILITIES AT SAHID UNIVERSITY SURAKARTA - Rifai, Dian Muhammad; Seftianingsih, Dina Kristiana; Rafia, Indy (ITB AAS Indonesia Surakarta, 2024)
Students with special needs need help understanding English vocabulary due to limited hearing and communication skills. Therefore, the proposer provides an alternative solution to improve learning through e-flipbooks based on local wisdom. The purpose of this study is to (1) Describe the mapping of the needs of students with disabilities regarding English learning materials for students with disabilities at Sahid University Surakarta and (2) Describe the development of e-flipbooks based on local wisdom for teaching English vocabulary to students with disabilities at Sahid University Surakarta. This model development research begins with a need analysis mapping the needs of students with disabilities in learning English, especially regarding vocabulary. Furthermore, the 4D development model (define, design, develop and disseminate). With the convenience of e-flipbook teaching media based on local wisdom, learners with disabilities can use this teaching media to understand English vocabulary more quickly.